2022
DOI: 10.1002/biof.1891
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1: A key endogenous inhibitor of neuroinflammation

Abstract: After the initiation of inflammation, a series of processes start to resolve the inflammation. A group of endogenous lipid mediators, namely specialized pro‐resolving lipid mediators is at the top list of inflammation resolution. Resolvin D1 (RvD1), is one of the lipid mediators with significant anti‐inflammatory properties. It is produced from docosahexaenoic acid (omega‐3 polyunsaturated fatty acid) in the body. In this article, we aimed to review the most recent findings concerning the pharmacological effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…PGD2 has been proposed to participate in diabetes‐associated brain dysfunction (Yang et al., 2021). Resolvin D1, which is a lipid mediator with anti‐inflammatory properties (Roohbakhsh et al., 2022), was found reduced in the hippocampus, together with its precursor 17‐HDoHE, by HSL deletion upon HFD but not CD feeding. In addition to supporting previous observations on changed levels of the endocannabioids AEA and 2‐LG in the brain of HSL−/− mice (Skoug et al., 2022), we now observed that levels of several acylethanolamides tended to increase in the hippocampus with HSL deletion, namely PEA, OEA, and SEA.…”
Section: Discussionmentioning
confidence: 99%
“…PGD2 has been proposed to participate in diabetes‐associated brain dysfunction (Yang et al., 2021). Resolvin D1, which is a lipid mediator with anti‐inflammatory properties (Roohbakhsh et al., 2022), was found reduced in the hippocampus, together with its precursor 17‐HDoHE, by HSL deletion upon HFD but not CD feeding. In addition to supporting previous observations on changed levels of the endocannabioids AEA and 2‐LG in the brain of HSL−/− mice (Skoug et al., 2022), we now observed that levels of several acylethanolamides tended to increase in the hippocampus with HSL deletion, namely PEA, OEA, and SEA.…”
Section: Discussionmentioning
confidence: 99%
“…44 Similar to TBI, inflammation and apoptosis are key processes involved in AD pathology. [145][146][147] Of note, the underlying mechanism for some compounds with therapeutic potential in AD is apoptosis inhibition. 148,149 As mentioned before, several studies have shown cholesterol efflux is impaired in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, ABCG1‐KO mice showed memory deficits, motor dysfunction and brain lesion volume more than control TBI mice 44 . Similar to TBI, inflammation and apoptosis are key processes involved in AD pathology 145–147 . Of note, the underlying mechanism for some compounds with therapeutic potential in AD is apoptosis inhibition 148,149 .…”
Section: Discussionmentioning
confidence: 99%
“…6 Resolvin D1 (RvD1) is apparently recognized as one of the lipid mediators and holds relatively potent antiinflammatory activities. 7 It is generated from docosahexaenoic acid (DHA) in phospholipid-rich tissues. 8 A significant reduction of RvD1 expressions was proved in rat brain tissues after subarachnoid hemorrhage.…”
Section: Introductionmentioning
confidence: 99%